Designing a Real-Time Fuel Consumption Monitoring Dashboard for Ships - Andre Sahulata; Aditiya Hermawan (RUBINSTEIN, 2025)
Fuel usage on ships is a crucial aspect of maritime operations, affecting cost efficiency and sustainability. A calculation carried out by the operational team is required in order to obtain information about the ship's fuel usage. However, the method of calculating fuel usage that is still manual by sounding is still prone to calculation errors and inefficient. Therefore, a system is needed that can assist the operational team in calculating and obtaining fuel usage data quickly and efficiently. This research aims to design a dashboard monitoring system that can monitor ship fuel usage in real-time. Real-time monitoring is important for quick identification of inefficiencies, ensuring safety, and supporting timely decision making. This system can assist the operational team in obtaining data and information on fuel usage more quickly and accurately. The methodology used in this research includes analyzing system requirements, designing system architecture, and implementing dashboard monitoring software. The result of this research is a dashboard system that is able to provide real-time information about fuel usage, making it easier for the operational team to monitor and make decisions. With this system, the efficiency of fuel usage can be increased and the pros of fuel usage can be improved.